(untitled) (Research, Society and Development, 2020)
This work aims to identify the level of sustainability of the solid waste management system adopted on the island of Cotijuba-Pa. For this, the model of matrix of sustainability indicators proposed by Santiago and Dias (2012) was selected, this can be used as an assessment tool in solid waste (SW) management. The selected matrix is composed of 42 indicators, it was deemed necessary to adapt it to the reality of the place, which was developed by professionals in the area of sustainability and solid waste from the Instituto Federal do Pará - Belém and the Geological Service of the Brazil - Belém, using the Delphi method. Thus, 5 indicators were removed from the matrix, and 1 was added, resulting in 38 indicators in the adapted matrix. For the score of the matrix indicators, 2 questionnaires were applied, one for those responsible for the management of waste in Cotijuba and another for the island community. The results showed that the local SW system had a score of 5.53, which classifies it with average level of sustainability. Therefore, the adaptation and subsequent application of the matrix proved to be efficient for this study, however, even with the average level reached, there was a need for improvement in the island’s management system, especially in the selective collection service by cooperatives and associations of scavengers.